The Guideline of the Application of Buddhist Principle for Resolving the Drug Adducting: A Case Study of the Youth in Juvenile Observation and Protection of Buriram Province - Pavijjo, Phra Pravit; Suvaco, Phramaha Phocana; Arnando, Phramaha Thanorm (Academic MCU Buriram Journal, 2024)
The purpose of this research were: 1) study the problem of children and youth with drugs in juvenile observation and protection centers. Buriram Province 2) study Buddhist principles regarding solving drug problems among children and youth, and 3) study guidelines for applying Buddhist principles to solving drug problems among children and youth in juvenile detention and protection centers. Buriram Province. This research is quantitative research. By designing a tool to survey the opinions of children and youth in correctional facilities. Caregivers and parents, a total of 25 people, were analyzed and presented descriptively. The research results found that: 1. The problems of the youth related to drugs in the Juvenile Observation and Protection of Buriram Province was very high of all numbers. The mean score ( ) was 62. However, having considered the criteria established, the problems of the youth related to drugs in the Juvenile Observation and Protection of Buriram Province is very high of all numbers. 2. The Buddhist principles for solving drug problems of the youth were very high of all numbers. The mean score ( ) was 4.07. However, having considered the criteria established, the Buddhist principles for solving drug problems of the youth was very high. 3. Guidelines for applying Buddhist principles to solve the drug problem of children and youth in juvenile observation and protection centers. Buriram Province Overall, 3 items were at the highest level. The rest were at a very high level. The average was 4.16 if considered according to the set criteria. Guidelines for applying Buddhist principles to solve the drug problem of children and youth in juvenile observation and protection centers. Buriram Province Overall, 3 items were at the highest level. Other than that, all items were at a high level.